Alkaline sulfite anthraquinone and methanol pulps from bamboo for papermaking applications - Abdallah, Areej Fathelrahman; Jawaid, Mohammad; Mohamed, Ainun Zuriyati; Md. Tahir, Paridah; Abdullah, Ummi Hani (Springer Science and Business Media Deutschland GmbH, 2024)
Bamboo is a versatile and fast-growing plant that generates cellulose with long fibers. This study examined the fiber morphology, chemical composition, and pulp and paper qualities of the bamboo Oxytenanthera abyssinica culm. The purpose was to assess their potential as an alternative feedstock for pulping and papermaking. The fiber characteristics were determined using the maceration method and the chemical analysis using the TAPPI standard method. The bamboo chips were pulped via the alkaline sulfite anthraquinone methanol (ASAM) pulping process, which involved charges of 15, 17, and 19% alkali, 15% methanol, 0.1% antraquinone, and 170 °C cooking temperature for 90 min. The screened yield went through the beating process at 2000, 4000, 6000, and 8000 revolutions. The mechanical properties of the hand sheets (60 g/m2) laboratory scale papers were assessed in accordance with TAPPI standards. The results showed that the bamboo fiber’s length is 1835 μm similar to those of softwood, and had led to stronger paper properties. The flexibility and Runkel ratios, at 51.71 and 0.94, respectively. Besides, the bamboo contained 71.25% holocellulose, 50.19% cellulose, and 25.67% lignin. The highest tensile index and burst index, calculated at 75.13 and 78.71 Nm/g and 7.10 and 7.40 kPa.m2/g respectively, were produced by the optimum pulp yield (45.24%) under 17% active alkali and kappa number 11.70 in 6000 and 8000 revolutions. We conclude that bamboo, with its excellent fundamental characteristics and the pulps derived from it through the ASAM pulping process, are suitable for the application of packaging paper grades.